Software to determine the production costs of seasonal crops in the central coastal areas of Peru - Rojas Rojas, Vicente Luis (2019)
The main objectives were: to program a software to calculate the costs of seasonalcrop production per hectare; to create a database of inputs, written and verbalagriculture technical information for the central coastal areas, and to validate thesoftware surveyed in a user satisfaction tested to students and academic staff involvedinto agriculture. It allow users to determine the sowing rate per hectare, number offertilizer bags according to NPK formulas, the current input costs, investment costsand profitability in one cropping hectare. The software considered the income, userpassword, initial presentation, general information to register a crop, record of specificdata defined by agriculture tasks, review, correction or adding data from direct andindirect costs, economic analysis, rate of return, final report in local currency (soles)or dollars, and printing the sheet production costs per hectare. It was concluded that98 % of respondents said that the software was friendly and 84 %, it was a successfulprogram to fill the needs of users engaged in agriculture. The software is friendly, easyto use and provides adequate support to users